PERENCANAAN PENYEDIAAN ENERGI DI WILAYAH LAMPUNG MENGGUNAKAN PERANGKAT LUNAK LONG-RANGE ENERGY ALTERNATIVES PLANING SYSTEM (LEAP) - Budi Waluyo; Harmen Burhanuddin; . Martinus (Jurnal Ilmiah Teknik Mesin, 2013)
Lampung province is a region with a strategic location as a gateway entrance and exit of the economy from the island of Java to Andalas or vice versa. Beside of that the potential of vast natural resources enough to serve as the foundation and development capital, including potential energy resources. Energy needs from year to year increased significantly. if fixed transport link between the islands of Java and Sumatra realized as expected energy demand will jump dramatically. Currently, most of the energy supply in Lampung are supplied from other areas such as Java, and other provinces in Sumatra. Therefore, it is necessary to forecast energy supply for several years to get the proper planning of energy supply to meet the energy needs at times to come. In this research study about projected energy supply in the region of Lampung using software LEAP (Long-range Energy Alternative Planning system) version 2008. The study is based on projections of existing energy needs and based on data from existing energy potential in the province of Lampung, such as coal, geothermal, biogas cow dung and buffalo, palm oil biodiesel and bioethanol sugar cane, sweet potatoes and cassava. The results showed that the supply of electricity from 2014 to 2030 was in excess of the electrical energy needs in the area of Lampung because of the operation of geothermal power plants. For biogas sector, projected at the beginning of the year to replace the LPG gas by 12% and at the end of the projection to 8% due to growth in cattle farm and buffalo are very small. For biodiesel sector, provision was 64% at the beginning of the projection, but declined at the end of the projection to 30% due to the growth of oil palm area is very low. In bioethanol sector, from the beginning to the end of the projection is only able to help reduce gasoline consumption by 4%, due to bioethanol are just a mixture so they are less significant. It can be concluded that the new renewable energy which featured in Lampung province are geothermal energy, biogas manure and corn cob gasification.Keywords: energy projection, LEAP model, transformation of energy, renewable energy.